2014
DOI: 10.1016/j.ijid.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and quantitative microbial risk assessment of Cryptosporidium and Giardia in soil and air samples

Abstract: Soil and air inhalation and/or ingestion are important vehicles for these parasites. To our knowledge, the results obtained in the present study represent the first QMRAs for cryptosporidiosis and giardiasis due to soil and air inhalation/ingestion in Mexico. In addition, this is the first evidence of the microbial air quality around these parasites in rural zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…em amostras ambientais, tais como solo, vegetais, esgoto e fontes de água, evidenciando a presença de oocistos. Este agente vem sendo responsavél por surtos de origem alimentar e de veiculação hídrica em diversas regiões do mundo (Balderrama-Carmona et al, 2014;Dreelin et al, 2014;Hong et al, 2014;Moss et al, 2014). A detecção do Cryptosporidium spp.…”
Section: Resultsunclassified
“…em amostras ambientais, tais como solo, vegetais, esgoto e fontes de água, evidenciando a presença de oocistos. Este agente vem sendo responsavél por surtos de origem alimentar e de veiculação hídrica em diversas regiões do mundo (Balderrama-Carmona et al, 2014;Dreelin et al, 2014;Hong et al, 2014;Moss et al, 2014). A detecção do Cryptosporidium spp.…”
Section: Resultsunclassified
“…We are aware of only one previous study reporting detection of enteric protozoan parasites in air samples, from rural Mexico, by microscopy; the study reported 8 of 12 samples positive for Cryptosporidium and 10 of 12 samples positive for Giardia, possibly via aerosolization of soil 130 . By comparison we detected Giardia duodenalis via qPCR in 22% of samples in La Paz and 18% of samples in Kanpur, with 3 and 5 positive detections per 2000 m 3 air at each site respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The miniscule size of Cryptosporidium oocysts has the capability to disseminate across the air, where they could be inhaled and cause infection in humans and animals [174]. Inhalation of oocysts from contaminated air can infect the respiratory tract and manifest respiratory symptoms [175][176][177].…”
Section: Airborne Transmission Of Cryptosporidium Under Arid Climate mentioning
confidence: 99%
“…Inhalation of oocysts from contaminated air can infect the respiratory tract and manifest respiratory symptoms [175][176][177]. Cryptosporidium oocysts have been observed in 60% of the investigated air samples in Mexico [174]. Direct contamination with faecal material because of the lack of sanitary infrastructure results in a greater dispersion of soil via airborne dust during dry season, particularly in those places where people are exposed to large amounts of outdoor dust [174].…”
Section: Airborne Transmission Of Cryptosporidium Under Arid Climate mentioning
confidence: 99%
See 1 more Smart Citation